Silver-assisted colloidal synthesis of gold patchy particles with tunable patchiness - Bao, Huixin; Butz, Benjamin; Zhou, Zhou; Spiecker, Erdmann; Hartmann, Martin; Klupp Taylor, Robin (Langmuir, 2012)
Patchy particles possessing heterogeneous surface composition show great promise as self-organizing building blocks for new classes of hierarchical functional structures. A major hurdle is the scalable synthesis of stable patches on nanosized core particles with arbitrarily defined patch number and coverage. So far, few methods have been reported which could be expected to meet these challenges. Recently we described the heterogeneous nucleation and growth of silver patches on silica nanospheres via a template free colloidal route. The patches produced, although tunable in size and number and showing interesting plasmon resonant properties, were rather unstable and degraded rapidly during attempts to process them further. In the present work, therefore, we set out to explore if related approaches can be employed to produce patchy particles involving gold, which is known to be more stable. The differences between typical patch precursors Ag+ and [AuClx (OH)4-x]- and their respective interactions with amorphous silica make this a significant challenge. We show that preformed small silver patches in addition to the presence of a reducing agent are necessary for the formation of gold patches conformal to the silica nanosphere surface. Systematic study of the process parameters and their influence on the patchiness as well as in-depth analytical TEM investigation of the patch composition reveal that patches spread over the silica surface via a cycle of galvanic dissolution and redeposition of silver. The resulting gold patchy particles remain stable during subsequent storage or washing and display tunable plasmon resonances within the visible and near-IR spectrum.
EAM Import::2019-03-13